Hate speech compounds in the German immigration discourse on Twitter - Bick, Eckhard (Journal of Speech Sciences, 2025)
This paper examines the use of derogatory prefixes and productive compounding as linguistic vehicles of hate speech in German Twitter, with a special focus on ethnic and religious minorities, on the background of the European immigration crisis. The linguistic mechanisms discussed focus on both morphology and semantics and include slur expansion, stereotype-based pseudo-slurs, fusion words, narrative encoding and the use of metaphor, among others. Specifically, we identify and document five main stereotypes for recent Muslim immigrants, as well as  the main derogatory narration metaphors used in the German immigration discourse (e.g. disease, disaster, war). We discuss and classify over 500 individual lexical examples and tweet fragments, showing how pejorative word elements (e.g. animal tropes) are amalgamated with target group connotaters to achieve various desired effects, both denotative and connotative, as well as humour-based techniques such as puns, irony and understatement. The work is based on an unabridged, grammatically and semantically annotated 2 billion word Twitter corpus, harvested between 2017 and 2019.